Challenges in Information Management Among Engineering College Librarians in Andhra Pradesh - Kumar, Kutty (Access: An International Journal of Nepal Library Association, 2025)
This research explores the obstacles encountered by librarians in the administration of information resources within engineering college libraries across Andhra Pradesh. Using a structured survey methodology, data were collected from a range of institutions—government, private, and minority-run—to identify shared information management (IM) challenges. Findings reveal significant impediments such as inadequate funding, scarcity of qualified personnel, hesitancy toward adopting technological advancements, and substandard infrastructure. These factors collectively undermine the efficient organization, retrieval, and dissemination of information, weakening library service quality. The study stresses the necessity for strategic reforms, including enhanced training initiatives, greater financial support, and the adoption of advanced information technologies. Addressing these barriers could strengthen IM practices and better support the academic and research activities of library users.